MEDICINAL PLANT - ALOE VERA (ALOE BARBAODENSIS) (British Journal of Global Ecology and Sustainable Development, 2024)
Exploring medicinal plants and their attributes for traditional medicine remains a prominent research area. This paper investigates the botanical classification, chemical components, medicinal properties, and indigenous medicine applications of Aloe, focusing on Aloe Barbadensis.